Experiences and possibilities in a curricular internship in collective health in nutrition (Research, Society and Development, 2020)
The present study aimed to socialize the academic experience regarding the diversity of views regarding the curricular internship in public health nutrition. This is a report of the student experience in the curricular internship in public health in the undergraduate course in nutrition at a Municipal Health Center, located in the West of the State of Rio de Janeiro in the period from March to July 2018. The experience lived in the curricular internship in public health, the student was given an opportunity to look through the lens of the nutritionist in the field of public health through different lenses, learning that the professional's attributions transcend the mere dietary prescription, enabling and implementing the necessary skills so that the future graduate can to act in a critical and reflective manner in their daily professional practice. The experience in this field of curricular internship in public health allowed the development of a critical and reflective look at the contributions of the nutritionist in a Municipal Health Center, analyzing that this professional, like any other member of the multidisciplinary team, has a significant contribution to the health process-disease.